Mandibular radiomorphometry analysis of children with HIV and healthy individuals on digital panoramic radiographs by age and sex - Alongsyah Zulkarnaen Ramadhan; Indra Gunawan; Ria Noerianingsih Firman; Farina Pramanik; Irna Sufiawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: The chronic systemic inflammatory process of HIV Human Immunodeficiency Virus) infection in children leads B cell activity to accelerate the osteoclastogenesis process, which results in bone alterations. Long-term usage of highly active antiretroviral medication results in decreased bone quality in HIV patients (HAART). Digital panoramic images are useful for radiomorphometric analysis of the mandibular macrostructure. Mandibular bone is a bone quality analysis that is often performed. Materials and Methods: This study comprised 86 digital panoramic radiographs of pediatric HIV patients and healthy persons. Secondary data in the form of digitized conventional panoramic radiographs of 43 pediatric HIV patients and 43 healthy individuals without clinical symptoms of HIV disease were utilized as a reference. Results: Mandibular morphometry values by sex in children with HIV and healthy adults showed (MCI) p-value 0.009, (GMI) p-value 0.934, (GI) p-value 0.584, (Go-Co) p-value 0.090, and (Co-M) p-value 0.919. Meanwhile, the results of the study with mandibular morphometric values ​​between children with HIV and healthy individuals index based on age revealed (MCI) p-value 0.490, (GMI) p-value 0.657, (GI) p-value 0.080, (Go-Co) p-value 0.147, (Co-M) p-value 0.158 Conclusion: Mandibular morphology differed between HIV-infected children and healthy persons as measured by digital panoramic radiographs, with changes in mandibular resorption thickness, mandibular bone width, and mandibular bone thickness. Furthermore, there were no differences in values, height, and length of the mandible, as well as variances based on age and sex.